Mucin-degrading gut commensals isolated from healthy faecal donor suppress intestinal epithelial inflammation and regulate tight junction barrier function - Pan, Mingfang; Barua, Nilakshi; Ip, Margaret (Frontiers in Immunology, 2022)
The intestinal epithelium surface is covered by a layer of mucus that harbors a complex and dynamic population of bacteria termed gut microbiota. In particular, some gut bacteria have the ability to degrade the mucin glycan for nutritional sources. However, the bacterial diversity of mucin-degrading bacteria in human gut microbiota and their role in the gut remains unclear. In this study, we characterized the diversity of mucin-degrading bacteria in the human gut microbiota by an established cultivation-based molecular profiling method. The results showed the gut commensals having the mucin degrading ability were widely distributed in the gut microbiota and were more abundant than previously thought. In addition, many previously uncharacterized mucin degraders were isolated from faecals samples, suggesting the mucin-degrading gut commensals were underappreciated. To gain a better understanding of the interaction between these mucin-degrading gut commensals and the host, the effect of the commensals on intestinal epithelial cells were examined, and the results revealed that the commensals (8 Bacteroides spp., 2 Parabacteroides spp, Akkermanisa muciniphila and Bifidobacterial dentium) incited low level of inflammatory response (IL-8 and TNF-α) but suppressed the inflammatory response induced by E. coli through downregulating the NF-κB pathway. The presence of gut commensals also showed potential in enhancing the epithelial tight junction (TJ) barrier function through regulating the mRNA expression of TJ protein genes such as Zo-1, Occludin, Claudin-1 and E-cadherin. Furthermore, the presence of commensal bacteria P. distasonis, B. thetaiotaomicron and A. muciniphila completely or partly restored the pro-inflammatory cytokine IL-1β induced TJ barrier disruption. In conclusion, these findings indicate that mucin-degrading gut commensals were widely distributed in the gut microbiota and showed anti-inflammatory effect against pathogen infection and potential in modulating the epithelial barrier function.